Building brands with effective shopper marketing - Masterson, Chris (Henry Stewart Talks, 2011)
Current landscape of shopper marketing, A shopper marketing approach, The bottom line, Brands and shopper marketing, The UK market, Customer support, Collaborate, not concede, Bakery case study, The look of success, Building brands